STRATEGIC HUMAN RESOURCE PLANNING AND ITS ROLE IN SUSTAINING TELECOMMUNICATION FIRMS IN RIVERS STATE - Nwachukwu , Chukwuemeka Daniel; Nwankwo , Chinedu Ikechukwu (Ayden International Journal of Education and Social sciences, 2025)
This study examines the relationship between human resource planning and organisational sustainability. Crosssectional research survey was employed as a research design. Target populated comprises of selected telecommunication firms operating in Port Harcourt. Accessible population consists of five telecom firms in Port Harcourt using a simple random sampling technique. 125 supervisors, human resource managers and general managers were surveyed. Sample size is 95 using Krejcie and Morgan (1970). 95 copies of questionnaire were distributed. 82 copies of the questionnaire were completely filled and returned for data analysis. Required number of people, skill of individual, age, and culture were measured on a 5-point Likert Scale ranging from 5-Great extent, 4-Moderate extent, 3-low extent, 2very low extent, 1Not all. Spearman’s Rank Correlation Coefficient was used for data analysis with the aid of statistical package for social sciences (SPSS 22.0). The study f ound that human resource planning has a significant relationship with organisational sustainability. The study concludes that human resource planning measured in terms of competence, age and culture enhances organisational sustainability. One of the recomm endations is that human resource professionals should consider the competence of each applicant very seriously for organization to be sustainable